GAMBARAN KADAR LOW DENSITY LIPOPROTEIN (LDL) PADA REMAJA PEROKOK DAN BUKAN PEROKOK DI DUSUN BUYAN, DESA PANCASARI, KECAMATAN SUKASADA, BULELENG, BALI - Ni Made Restina Juliani; I Putu Oka Dharmawan; Putu Ayu Parwati (Stikes Wira Medika Bali, 2017)
Introduction: Low Density Lipoprotein (LDL) is a type of low-density lipoprotein and the most widely transported cholesterol in the body. Increased levels of LDL in the body can be affected by genetics, age, gender, obesity, physical activity, lifestyle, drug consumption and smoking. Substances in a cigarette can cause an increase of LDL levels. Increased of LDL cholesterol levels can cause Coronary Heart Disease (CHD). The purpose of this research is to know the description of Low Density Lipoprotein (LDL) levels on smoker and non-smoker adolescent in Buyan Hamlet, Pancasari Village, Sukasada District, Buleleng Bali. Method: The type of this research is descriptive. This research was conducted in April-May 2017, which used fasting blood samples of 42 respondents. Result: From the average result of LDL level in smoker adolescent that is 134,91 mg/dL higher than the average of LDL level in non-smoker adolescent that is 74,90 mg/dL. The result of LDL cholesterol levels was determined by 21 smoker adolescent respondents with the close to optimal category (100-129 mg/dL) as many as 9 people (42,8%), and 12 people (57,3%) with worry category (130-159 mg/dL). Whereas in 21 non-smoker adolescent respondents obtained result of LDL cholesterol level test with optimal category (<100 mg/dL) counted 18 people (87,71%) and 3 person (14,30%) with close to optimal category (100-129 mg/dL). Discussion: Based on the results of this research can be concluded that in smoker adolescent obtained LDL levels with close to optimal category and worrying whereas in non-smoker adolescents obtained LDL levels in the optimal category and close to optimal.